2016
DOI: 10.1016/j.corsci.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale corrosion behavior of polycrystalline copper fine wires in dilute NaCl solution investigated by in-situ atomic force microscopy

Abstract: In this study, nanoscale corrosion behavior of copper fine wires in dilute NaCl solution is studied by atomic force microscopy and electron backscatter diffraction technique. The dissolution rate of the grains constituting the wires strongly depends on their crystallographic orientation. In pure water, the dissolution rate increases in the order of (111) < (001) < (110). Addition of Cl − dramatically increases the dissolution rate of the (111) surface to alter the order to (110) ≈ (001) ≈ (111) at 0.1 mM. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Inorganic halide salts are well known for inducing nanostructuring process in copper surfaces . Thus, we decided to study the influence of the bromide counteranion in 1‐Br 2 on the formation of the observed nanocubes at the electrode surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic halide salts are well known for inducing nanostructuring process in copper surfaces . Thus, we decided to study the influence of the bromide counteranion in 1‐Br 2 on the formation of the observed nanocubes at the electrode surface.…”
Section: Resultsmentioning
confidence: 99%
“…Inorganic halide salts are well known for inducing nanostructuring process in copper surfaces. [36] Thus,wedecided to study the influence of the bromide counteranion in 1-Br 2 on the formation of the observed nanocubes at the electrode surface.W hen ap olycrystalline copper electrode is left in contact with an aqueous solution of KBr (20 mm)f or 5min, and then subjected to 3m easurements of potentiostatic electrochemical impedance spectroscopy (PEIS), AFM images show the presence of nanocubes similar in shape to those formed with additive 1-Br 2 ,w ith ah eight of ca. 80-90 nm ( Figure S17a).…”
Section: Resultsmentioning
confidence: 99%
“…Copper is one of the most important materials in the industry owing to its relatively noble properties. The anodic polarization of copper in acidic, neutral, and alkaline chloride media has received considerable attention in the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. As the electro-dissolution of Cu is found to be complex, the various mechanisms proposed can be applied for chloride electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Kear et al, summarized copper corrosion in chloride electrolytes and concluded three different models of the initial electro-dissolution reactions of bare copper [1]. There are three possible initial reaction cases of the anodic polarization behavior of pure copper in acidic and neutral chloride media [1,10,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation